Etiology of Various Dental Developmental Anomalies -Review of Literature - Monika Rohilla (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
The development of the tooth involves many complex biological processes, including epithelial-  esenchymal interactions, differentiation, morphogenesis, fibrillogenesis and mineralization. After 37 days of development, a continuous band of thickened epithelium forms around the mouth in presumptive upper and lower jaws from the fusion of separate plates of thickened epithelium-primary epithelial band and gives rise to vestibular lamina and dental lamina [1].